Influence of financial resources and marketing strategy on the competitiveness of food and beverage enterprises - Ngoc, Doan Thi Nguyet; Dung, Vu Quoc; Ly, Pham Huong; Lan, Vu Thi; Hieu, Pham Van (Edelweiss Applied Science and Technology, 2025)
The food and beverage industry is one of the most important sectors of the Vietnamese economy, not only because of its contribution to GDP but also because it creates millions of jobs for workers. With a large population, a rich culinary culture, and a potential domestic market, this industry is on the rise and attracts significant investment interest from both domestic and international investors. The purpose of this study is to evaluate, analyze, and measure the influence of financial resources and marketing strategies on the competitiveness of food and beverage (F&B) enterprises in Vietnam, and to propose recommendations to help F&B enterprises in Hanoi improve business performance and expand their scale. Methodology involved a survey conducted with the participation of employees from F&B enterprises in Vietnam, including members of the board of directors, accounting departments, and sales departments. However, only 250 survey forms met the requirements and were processed. Analytical methods such as descriptive statistics, Cronbach’s alpha coefficient analysis, exploratory factor analysis (EFA), correlation analysis, and regression models were used to test and measure the scales. The research results indicate that financial resources and marketing strategies positively influence the competitiveness of F&B enterprises in Vietnam to varying degrees. This study utilizes the contents of financial resources and marketing strategies of firms, along with the firms’ competitiveness based on prior research in the field. In the context of digital technology, food safety, and essential consumer needs, these variables serve as useful solutions for firms.